2007
DOI: 10.1182/blood-2006-12-064683
|View full text |Cite
|
Sign up to set email alerts
|

The C-MYB locus is involved in chromosomal translocation and genomic duplications in human T-cell acute leukemia (T-ALL), the translocation defining a new T-ALL subtype in very young children

Abstract: The C-Myb transcription factor is essential for hematopoiesis, including in the T-cell lineage. The C-Myb locus is a common site of retroviral insertional mutagenesis, however no recurrent genomic involvement has been reported in human malignancies. Here, we identified 2 types of genomic alterations involving the C-MYB locus at 6q23 in human T-cell acute leukemia (T-ALL). First, we found a reciprocal translocation, t(6;7)(q23;q34), that juxtaposed the TCRB and C-MYB loci (n ‫؍‬ 6 cases). Second, a genome-wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
222
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(239 citation statements)
references
References 65 publications
16
222
1
Order By: Relevance
“…This is surprising because there is generally strong correlation between transactivation and transformation by c-Myb (Hu et al, 1991), and the importance of functional co-activation by CBP/p300 (Pattabiraman et al, 2009) and menin/MLL (Jin et al, 2010) has been shown. In cancers linked to aberrations involving the MYB locus, increased c-Myb dosage, and hence activity, seems to be a common theme (Clappier et al, 2007;Lahortiga et al, 2007;Persson et al, 2009). Nevertheless, the 2KR and ANAA mutants described here seem to partially dissociate transactivation from transformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is surprising because there is generally strong correlation between transactivation and transformation by c-Myb (Hu et al, 1991), and the importance of functional co-activation by CBP/p300 (Pattabiraman et al, 2009) and menin/MLL (Jin et al, 2010) has been shown. In cancers linked to aberrations involving the MYB locus, increased c-Myb dosage, and hence activity, seems to be a common theme (Clappier et al, 2007;Lahortiga et al, 2007;Persson et al, 2009). Nevertheless, the 2KR and ANAA mutants described here seem to partially dissociate transactivation from transformation.…”
Section: Discussionmentioning
confidence: 99%
“…The MYB locus is rearranged in several human neoplasias, with increased expression as a frequent outcome. This can be caused by translocation, leading to deregulation of the MYB gene, as in childhood T-cell acute lymphoblastic leukemia (Clappier et al, 2007), or stabilization of MYB mRNA, as in adenoid cystic carcinomas of the breast, head and neck (Persson et al, 2009). Local duplication of MYB has also been reported with another subgroup of T-cell acute lymphoblastic leukemia (Clappier et al, 2007;Lahortiga et al, 2007) and in a subgroup of acute myelomonocytic leukemia (Murati et al, 2009).…”
mentioning
confidence: 99%
“…Although isolated cases of amplification and truncation of MYB have also been described some time ago in human leukemias (8,9), the use of newer, higher-resolution genomic technologies is suggesting that MYB contributes more frequently to these diseases. Thus, chromosomal translocation and genomic duplications of MYB have been identified in human T-cell acute leukemia (10,11); more recently, a gain of the MYB locus has been reported in acute myelomonocytic leukemia (12).…”
Section: Introductionmentioning
confidence: 99%
“…However, expression is also detected in smooth muscle cells [199], gut epithelium [200], hair follicles [201] and several non-hematopoietic carcinomas such as small cell lung carcinoma [202], colon carcinoma [203], breast carcinoma [204], and neuroblastoma [205], as well as Tcell acute lymphoblastic leukemia [206,207]. Interestingly, expression of Myb mRNA is abundantly expressed in hematopoietic progenitor cells and expression decreases as cells approach terminal differentiation [194,[208][209][210].…”
Section: Expression and Function Of Myb During Hematopoiesismentioning
confidence: 99%
“…Gene duplication of Myb or translocation of the Myb locus into the Tcrb locus is detected in patients with T-cell acute lymphoblastic leukemia (T-ALL), a neoplastic disorder of progenitor T cells [206,207]. The Myb-Tcrb translocation, which defines a new subset of T-ALL, places Myb expression under the control of Tcrb regulatory elements suggesting that continuous expression of c-Myb during thymopoiesis had an adverse effect characterized by increased expression of genes involved in cellular proliferation [206]. Together this data demonstrated that regulation of Myb expression is crucial during thymopoiesis;…”
Section: Expression and Function Of Myb During Hematopoiesismentioning
confidence: 99%